DYNAMIC ANALYSIS OF THE MATHEMATICAL MODEL FOR STUNTING WITH NUTRITION AND EDUCATION INTERVENTIONS - Sabran, La Ode; Annur, Lathifah; Ratu Laura, Athisa (PATTIMURA UNIVERSITY, 2025)
This study presents a mathematical model that analyzes the impact of nutrition and education interventions on stunting prevalence. Nutritional interventions are carried out on toddlers indicated to be stunted and toddlers who are healthy but susceptible to stunting. Meanwhile, education is given to the toddler's mother compartment. The model categorizes the toddler population into four compartments: susceptible, stunting-indicated, permanently stunted, and non-stunted. Similarly, the maternal population is categorized into three compartments: susceptible mothers, mothers exhibiting poor parenting practices, and educated mothers. The model's equilibrium point comprises two distinct states: a stable stunting-free equilibrium point when the basic reproduction number (R0) is less than one and a stable stunting-endemic equilibrium point when R0 is more significant than one. Sensitivity analysis reveals that the parameters that significantly influence the reduction or increase in stunting cases are the rate of nutritional intervention for children and the intensity of education for mothers. Numerical simulations demonstrate that implementing nutritional intervention activities and continuous education programs can effectively eliminate stunting cases in the population. The simulation results show a high number of stunting cases, reaching 161,566 cases in the population, due to poor education and poor nutritional interventions. In contrast, education programs and effective nutritional interventions eliminate stunting from the population. However, it takes longer.